2005
DOI: 10.1521/suli.2005.35.5.536
|View full text |Cite
|
Sign up to set email alerts
|

Utah Youth Suicide Study: Psychological Autopsy

Abstract: We conducted a psychological autopsy study to further understand youth suicide in Utah. While traditional psychological autopsy studies primarily focus on the administration of psychometric measures to identify any underlying diagnosis of mental illness for the suicide decedent, we focused our interviews to identify which contacts in the decedent's life recognized risk factors for suicidal behavior, symptoms of mental illness, as well as barriers to mental health treatment for the decedent. Parents and friends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 33 publications
2
57
1
3
Order By: Relevance
“…It has been suggested that family and friends may be best suited to act as gatekeepers based on their close relationship with those at risk for suicide. 13 In…”
Section: Gatekeeper Trainingmentioning
confidence: 99%
“…It has been suggested that family and friends may be best suited to act as gatekeepers based on their close relationship with those at risk for suicide. 13 In…”
Section: Gatekeeper Trainingmentioning
confidence: 99%
“…Furthermore, despite these youths having a prescription for psychotropic medications, these medications were not detected at therapeutic or even subtherapeutic levels. 4 In order to investigate the potential barriers to treatment of underlying mental health disorders, 49 families of suicide completers were interviewed, totaling 270 community contacts. Presented with 20 possible barriers to mental health treatment, with the option to write in additional barriers, the 5 primary barriers to treatment reported by these families were related to stigma (Table 1).…”
mentioning
confidence: 99%
“…In some of the studies, they did not exclude those who had an injury to death period of less than 3 days. 46 Antidepressants with a short half life (such as fluvoxamine or sertraline) may substantively been metabolised if the injury to death interval is more than 72 h. 54 Further, it has been suggested that antidepressant withdrawal may be a mechanism that increases suicidal behaviours. 55 It can also be argued that those who are on antidepressants are less likely to die if they overdose only on their prescribed antidepressants, given the low overall lethality of newer antidepressant agents.…”
mentioning
confidence: 99%